ONLINE TEACHING MANAGEMENT SYSTEM FOR BASIC EDUCATION LEVELS OF GENERAL PRIVATE SCHOOLS UNDER THE OFFICE OF EDUCATION KHON KAEN PROVINCE - Kositpimanvech, Ekkarach; Phansawang, iraporn; Pimthong, Adul; Getprom, Chatchai; Kositpimanvech, Chayanit (Journal of Buddhist Education and Research (JBER), 2024)
Abstract This research article the objective is to develop an online teaching management system for basic education in general private schools. Under the jurisdiction of the Khon Kaen Provincial Education Office. How to conduct research It consists of the study of concepts, principles, theories and related research. The researcher asked experts for opinions. Teaching system design and educational technology in the field of design and development of educational media and computers, 20 people were purposively selected. By inquiring using the Delphi technique for 3 rounds, expert opinions with a median equal to or greater than 3.50 and an interconal range equal to or less than 1.50 were used to develop an online teaching management system for basic education levels. General private school Under the jurisdiction of the Khon Kaen Provincial Education Office. The teaching management system developed has been certified by 5 experts. Statistics used in the research include frequency, percentage, arithmetic, standard deviation, mean, median and interconal range. The results of the research found that the online teaching management system for the basic education level of private schools, general category, under the Khon Kaen Provincial Education Office It consists of the following details: Online teaching planning consists of 1) philosophy, aspirations, policies, principles 2) Problems in organizing teaching and learning 3) Curriculum 4) Student needs 5) Infrastructure Designing online teaching consists of 1) determining teaching objectives, 2) analyzing students, 3) analyzing teaching content, 4) determining learning methods and teaching activities, 5) determining teaching media and infrastructure, and 6) Set management methods Producing online teaching kits consists of 1) planning the production of teaching kits, 2) choosing the type of lesson program, 3) preparing to produce the teaching kits, 4) producing the teaching kits, 5) testing the effectiveness of the teaching kits, and 6) packaging the teaching kits. Teach how to choose channels The system for conducting online teaching and evaluating learning achievement consists of 1) testing before class, 2) teaching, 3) controlling and checking. Follow up on academic results 4) Test after class There are also other important aspects, namely suitability, budget, impacts, problems and obstacles.